Hardening induced by dislocation core spreading at disordered interface in Cu/Nb multilayers. (15th July 2021) - Yang, Wenfan; Gong, Mingyu; Yao, Jiahao; Wang, Jiangwei; Zheng, Shijian; Ma, Xiuliang
Abstract: Atomistic scale interface structures could tailor the dislocation behaviors at interface, as well as interface strengthening. In this work, we design a disordered interface by introducing an ultrathin amorphous layer in the Cu/Nb multilayers. Compared to the sharp interface, the disordered interface can smear the impinging dislocation with relaxing the in-plane and out-of-plane Burgers vectors, thus inducing a remarkable hardening in the Cu/Nb multilayers. The findings not only prove the hardening effect induced by dislocation interface smearing, but also shed light on developing advanced materials with ultrahigh hardness via disordered interface. Graphical abstract: Image, graphical abstract